2013
DOI: 10.1017/s0003055413000415
|View full text |Cite
|
Sign up to set email alerts
|

Keeping the Public Purse: An Experiment in Windfalls, Taxes, and the Incentives to Restrain Government

Abstract: I t is widely believed that rents from windfall revenue undermine accountability. An enduring explanation is that windfalls free leaders from the need to tax, producing a quiescent population. Yet, there is little direct evidence of how windfalls and taxes affect citizen political action. I use novel revenue and information experiments to examine whether and why windfalls (compared to taxes) affect how citizens participate in politics. The experiments were embedded in a public awareness campaign conducted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(103 citation statements)
references
References 54 publications
3
99
0
1
Order By: Relevance
“…Subnational studies have shown that oil rents assist elected officials to prolong their stay in power through generous redistribution (irrespective of the quality of the services they provide; see Goldberg et al, 2008, for the US and Gervasoni, 2010a, 2010b. This is in line with Paler (2013) who uses experimental data from 1,863 villagers (from the Blora district in Indonesia)…”
Section: Other Variablessupporting
confidence: 85%
“…Subnational studies have shown that oil rents assist elected officials to prolong their stay in power through generous redistribution (irrespective of the quality of the services they provide; see Goldberg et al, 2008, for the US and Gervasoni, 2010a, 2010b. This is in line with Paler (2013) who uses experimental data from 1,863 villagers (from the Blora district in Indonesia)…”
Section: Other Variablessupporting
confidence: 85%
“…Tiebout-style explanations suggest that an increase in taxes will attract different types of citizens, but mobility costs in Brazil are likely too high for this mechanism to bite (Timmins and Menezes, 2005). The literature in political science argues that paying more taxes (or starting to pay taxes) makes citizens demand more from their government and/or spend more time monitoring elected politicians; this idea came up often during interviews with taxpayers and politicians (see for example Paler (2013)). In the absence of data on migration across municipalities over the period, citizens' preferences or endeavors to control their politicians these two mechanisms cannot be formally tested.…”
Section: B Mechanismsmentioning
confidence: 99%
“…Similarly, using survey data, McGuirk (2013) finds that higher perceived tax enforcement leads to higher demands for accountability in sub-Saharan Africa. Paler (2013), who conducts an experiment in an Indonesian region, finds that taxpayers tend to monitor and hold politicians accountable to a higher degree than those who do not pay taxes.…”
Section: Introductionmentioning
confidence: 99%